Urgent endoscopy in children: epidemiology in a large region of France - Norsa, Lorenzo; Ferrari, Alberto; Mosca, Alexis; Talbotec, Cecile; Campeotto, Florence; Lemale, Julie; Pigneur, Bénédicte; Viala, Jerome (Endoscopy International Open, 2020)
Background and study aims The real burden of urgent endoscopy in children has not been studied yet. Our aim was to evaluate the need for urgent endoscopy in children.Patients and methods Information was collected about all the calls that were received during the 24 hour on-call shift for pediatric endoscopy in the region of Ile-de-France (12.1 million inhabitants) during a 6 months period (February-July 2017).Results A total of 237 calls (19 calls/y/100,000 children) were collected regarding children of an average age of 3.2 years (range 2 days-18 years). Most of the calls (68 %) were for foreign body ingestions. Gastroscopy was required in 32 % of children: 24 % of those calling for foreign body ingestion, 48 % for gastrointestinal bleeding, 63 % for caustic ingestions (P = 0.01). The average time between the call and the urgent endoscopy were below the international recommendations for each situation.Conclusions Calling the endoscopist seems to have become a recurrent practice, although in most cases, urgent endoscopy did not appear necessary, especially for foreign body ingestion. This organization of pediatric endoscopy on call was able to guarantee the performance of urgent endoscopy in adequate timing for a highly populated region.